Targeting mTOR pathway: A new concept in cancer therapy - Advani S (Indian Journal of Medical and Paediatric Oncology)
This article highlights the current knowledge of mTOR biology and provides new insights into the role of mTOR in different cancers. An active mTOR coordinates a response in cell growth directly through its effects on cell cycle regulators and indirectly by sustaining nutrient supply into the cell through the production of nutrient transporters and also through the promotion of angiogenesis. A primary way that mTOR exerts its regulatory effects on cell proliferation is by controlling the production of cyclin D1. mTOR increases the translation of hypoxia-inducible factor 1 (HIF-1)/HIF-2. The HIF transcription factors drive the expression of hypoxic stress response genes, including angiogenic growth factors such as vascular endothelial growth factor (VEGF), platelet-derived growth factor b (PDGF- b), and transforming growth factor a (TGF-a). mTOR also increases the surface expression of nutrient transporters proteins. An increase in these proteins results in greater uptake of amino acids and other nutrients by the cell leading to adequate nutrient support to abnormal cell growth and survival. There is also emerging evidence that mTOR activation may play a role in promoting cell survival through the activation of antiapoptotic proteins that contribute to tumor progression. Given that the mTOR pathway is deregulated in a number of cancers, it is anticipated that mTOR inhibitors will have broad therapeutic application across many tumor types. Until now, no treatment demonstrated Phase III evidence after disease progression on an initial VEGF-targeted therapy in advanced renal cell carcinoma. Everolimus is the first and only therapy with Phase III evidence after failure of VEGF-targeted therapy. Everolimus is a once-daily, oral inhibitor of mTOR (mammalian target of rapamycin) indicated for the treatment of advanced renal cell carcinoma in patients, whose disease has progressed on or after treatment with VEGF-targeted therapy.